Scientific Ethics and the Moral Crisis in the Digital Age: Seeking Truth Amidst the Flow of Information: Scientific Ethics and the Moral Crisis in the Digital Age: Seeking Truth Amidst the Flow of Information - Amalia, Azizah Nur; Channan, Chadziq Abdul; Nabila, Kamilia Izzah; Affuzal Ulya, Mochammaad Ali Ubaidillah (Maliki Interdisciplinary Journal, 2026)
Digital transformation has shifted the way humans interact with humans and with information, starting from the way they search, how to obtain, share or even interpret the information they have obtained. Although it has many positive impacts, it is undeniable that it also has significant negative impacts. Such as information misinformation, the dissemination of personal data and the weakening of basic ethical values in the digital world. This article outlines how a moral crisis occurs when people do not understand enough about assessing information carefully in the midst of the current rapid flow of digital world. Through theoretical studies, this paper invites to restore scientific ethics as the basis for seeking the truth in the midst of the current flow of information, maintain the quality of public understanding of the importance of ethical foundations before entering the digital world, and create a healthier and safer digital space. This strengthening is the first step so that the community can receive, disseminate and interpret information based on a sense of responsibility.